Data sharing in low-resourced research environments. (1st September 2016) - Rappert, Brian; Bezuidenhout, Louise
Abstract : 'Open data' has recently emerged as a label for renewed attempts to promote scientific exchange. As part of such efforts, the posting of data online is often portrayed as commonly beneficial: individual scientists accrue greater prominence while at the same time fostering communal knowledge. Yet, how scientists in non-Western research settings assess such calls for openness has been the subject of little empirical study. Based on extended fieldwork with biochemistry laboratories in sub-Sahara Africa, this paper examines a variety of reasons why scientists opt for closure over openness with regard to their own data. We argue that the heterogeneity of research environments calls into question many of the presumptions made as part of open data. Inequalities in research environments can mean that moves towards sharing create binds and dilemmas. These observations suggest that those promoting openness must critically examine current research governance and funding systems that continue to perpetuate disparities. The paper proposes an innovative approach to facilitating openness: coupling the sharing of data with enabling scientists to redress their day-to-day research environment demands. Such a starting basis provides an alternative but vital link between the aspirations for science aired today as part of international discussions and the daily challenges of undertaking research in low-resourced environments.